Human Resources Readiness for Policies Electronic Government Online Licensing Services at the Investment Service and One-Door Integrated Services (DPMTSP) East Luwu District - Haerullah, Haerullah; Fatmawati, Fatmawati; Hakim, Lukman; Madani, Muhlis (International Conference on Sciences Development and Technology, 2022)
Reform of public services with a new mechanism of interaction between the government and society with changes in the service system that involve the public in decision- making. The purpose of this study is to analyze the readiness of human resource development in electronic government-based licensing services, constraints in their application, and find an electronic government development model in order to improve the quality of licensing services at the East Luwu Eats Investment and One-Stop Integrated Service (DPMPTSP) Office, using descriptive. Qualitative research methods. The results showed that the policy model for developing electronic government-based licensing services at DPMPTSP Eats Luwu Timur is at the transaction level, even though it is at the transaction level, but the support of service users in developing e-government-based services is still low, therefore, there is a need for collaboration and integration between the government, the community and related stakeholders in developing and optimizing the use of electronic government in East Luwu district government environment by developing a government-based electronic service model, people can be active participate in the policy formulation process, without being limited by time and space.